GAMBARAN KESEHATANI GIGI DAN MULUT LANSIA PADA POSYANDU LANSIA DI WILAYAH PUSKESMAS III DENPASAR SELATAN TAHUN 2OI3 - Eka Juliastuti; Anak Agung Gede Agung; I Nyoman Wirata (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2015)
A group of elderly people who are prone to caries and periodontal disease , tooth so that the elderly often lose teeth. Carries is universal disease that can happen to everyone. The impact of aging on dental health and oral marked increase in the loss of teeth , poor oral hygiene , periodontal disease , tooth root caries , erosion , abrasion and oral cancer. The purpose of this study was to describe the oral health of the elderly in the region elderly IHC Health center III South Denpasar in 2013.This study is a descriptive, cross sectional area of the elderly in IHC Health Centre III South Denpasar with a total sample of 90 people. Proportional sampling using random sampling.The results of this study indicate that the frequency of the elderly who experience caries 85.56 % and 14.44 % did not experience caries. The level of oral hygine respondents mostly with the criteria being totaled 57.78 % , of respondents with poor criteria and 42.22 % of the respondents did not find a good criteria. The number of teeth serve ≥ 20 on the respondents was 62.22 % with an average of tooth fuction on respondent between 20 to 22 teeth (21.70) from these results we can conclude that most of the elderly experience dental caries. Elderly who have a higher frequence of oral hygiene (OHIS value) is most commontly found in the criteria was not good while the criteria is not found on the respondent. The frequence of the number of teeh serve elderly ≥ 20 as much as 62.2%. Average dental fuction in the elderly has been in accordance with the national target set.Based on these conclusions it is recommended that the family helps to motivate the elderly to further improve dental hygiene and mouth as well as the local health centers are expected to mprovide information on how to maintain oral hygiene by providing counselling and dental health care of the elderly in elderly IHC Health Center Region III South Denpasar in periodically.